2011
DOI: 10.1021/mp2003658
|View full text |Cite
|
Sign up to set email alerts
|

New in Vitro Tools to Study Human Constitutive Androstane Receptor (CAR) Biology: Discovery and Comparison of Human CAR Inverse Agonists

Abstract: The human constitutive androstane receptor (CAR, NR1I3) is one of the key regulators of xenobiotic and endobiotic metabolism. The unique properties of human CAR, such as the high constitutive activity and the complexity of signaling, as well as the lack of functional and predictive cell-based assays to study the properties of the receptor, have hindered the discovery of selective human CAR ligands. Here we report a novel human CAR inverse agonist, 1-[(2-methylbenzofuran-3-yl)methyl]-3-(thiophen-2-ylmethyl) ure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 58 publications
1
36
0
Order By: Relevance
“…Phenobarbital showed the highest inductive response for CYP2C9 expression and activity in the HepatoPac model, perhaps owing to its dual activation of PXR and CAR. Phenytoin, a preferential hCAR transactivator (Küblbeck et al, 2011) failed to significantly increase CYP2C9 mRNA or activity in either culture model. A previous report by Sahi et al (2009) has also shown that phenytoin does not induce CYP2C9.…”
Section: Discussionmentioning
confidence: 77%
“…Phenobarbital showed the highest inductive response for CYP2C9 expression and activity in the HepatoPac model, perhaps owing to its dual activation of PXR and CAR. Phenytoin, a preferential hCAR transactivator (Küblbeck et al, 2011) failed to significantly increase CYP2C9 mRNA or activity in either culture model. A previous report by Sahi et al (2009) has also shown that phenytoin does not induce CYP2C9.…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, this compound was reported to be an mCAR agonist instead. However, other studies did not validate meclizine as being an hCAR inverse agonist [29, 30]. …”
Section: Car Inhibitorsmentioning
confidence: 99%
“…The mammalian two-hybrid assay measures the ligand-dependent interaction of CAR with a selected co-regulator peptide. This assay appears to be more sensitive in identifying weak or partial agonists that may elicit both co-activator and corepressor recruitment and very useful in dissecting the co-regulator profile of human CAR [ 57 ] and to gain support for human CAR/ligand interactions [ 35 , 63 ].…”
Section: Assays To Discover Novel Ligandsmentioning
confidence: 99%